Are bacterial infections a major cause of cardiovascular disease? - Kissinger, Dohn (Frontiers in Cardiovascular Medicine, 2024)
The Cholesterol Theory is the prevailing theory of cardiovascular disease (CVD). It proposes that CVD is caused by high levels of Low-Density Lipoprotein Cholesterol (LDL-C